The Development of An Art History in the UAE: An Art Not Made To Be Understood - Makhlouf, Sophie Kazan (London/NY; Anthem Press, 2025)
Work by artists from the United Arab Emirates (UAE), interviews and first-hand accounts form the core of this book about the development of the country$1 (Bs art history. Learning about artists and seeing how their practices fit into global art historical discourses can help viewers gain insight into an art not made to be understood.s
English
Keywords: Art industry- Development; N5300-7418 Visual Arts- History; UAE